Genetic polymorphism in psoriasis and its meaning for the treatment efficacy in the future - Osmola-Mańkowska, Agnieszka; Teresiak-Mikołajczak, Ewa; Skrzypczak-Zielińska, Marzena; Adamski, Zygmunt (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
The concept of personalized medicine is a new individualized approach which helps application of the targeted therapy. In fact, tailored medicine is mostly present in the field of life-threatening diseases such as oncology. However, skin diseases as such might be regarded as a potential area of implementation of this approach in the future. Stratified medicine in polygenetic and heterogeneous diseases, such as psoriasis, is more complex. Rapid development of science and novel molecular techniques led to better understanding of molecular pathogenetic pathways of many diseases including psoriasis. Identification of the particular immunopathogenetic pathways led to further development of targeted therapies such as biologic drugs. Actually the goal of individualized therapy is to determine the identical homogenous subgroups of patients, according to a biomarker, in which the response to that therapy will be the best and will carry the lowest risk of side effects. This review attempts to analyze the associations between polymorphisms of certain genes and the increased risk of developing psoriasis or psoriatic arthritis. The review of literature has also included the studies investigating the associations between gene polymorphisms and response to biologic therapy in psoriasis and psoriatic arthritis patients.